Polymer-sorted semiconducting carbon nanotube networks for high-performance ambipolar field-effect transistors - Schießl, Stefan Patrick; Fröhlich, Nils Gerrit; Held, Martin; Gannott, Florentina; Schweiger, Kai Manuel; Forster, Michael; Scherf, Ullrich; Zaumseil, Jana (ACS applied materials & interfaces, 2015)
Efficient selection of semiconducting single-walled carbon nanotubes (SWNTs) from as-grown nanotube samples is crucial for their application as printable and flexible semiconductors in field-effect transistors (FETs). In this study, we use atactic poly(9-dodecyl-9-methyl-fluorene) (a-PF-1-12), a polyfluorene derivative with asymmetric side-chains, for the selective dispersion of semiconducting SWNTs with large diameters (>1 nm) from plasma torch-grown SWNTs. Lowering the molecular weight of the dispersing polymer leads to a significant improvement of selectivity. Combining dense semiconducting SWNT networks deposited from an enriched SWNT dispersion with a polymer/metal-oxide hybrid dielectric enables transistors with balanced ambipolar, contact resistance-corrected mobilities of up to 50 cm2·V-1·s-1, low ohmic contact resistance, steep subthreshold swings (0.12-0.14 V/dec) and high on/off ratios (106) even for short channel lengths (<10 μm). These FETs operate at low voltages (<3 V) and show almost no current hysteresis. The resulting ambipolar complementary-like inverters exhibit gains up to 61.